ACTIVATING MARKETING WORD-OF-MOUTH BASED IN THE EFFECTIVENESS OF THE PHYSICAL AND SOCIAL ENVIRONMENT OF HEALTH SERVICE AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF PRIVATE HOSPITAL CUSTOMERS IN BABYLON GOVERNORATE (World Bulletin of Social Sciences, 2023)
The study aims to determine the effect of word-of-mouth marketing in activating the physical and social environment of service. A sample of (158) patients in private hospitals in Babil Governorate was selected to conduct the study. The study is based on a main hypothesis that (the word-of-mouth marketing practiced by patients can be activated through the effectiveness of the physical and social environment of the service). Empirical measures from previous studies were used to verify these hypotheses. A set of statistical tools were used to analyze and process the data through the simple correlation matrix, simple regression analysis, and the structural modeling equation to test the hypotheses of the study. The study reached a set of conclusions, the most important of which was (there is a positive and important impact of the physical and social environment of the service in disseminating and enhancing wordof-mouth marketing by the customer). In the light of the conclusions, a set of recommendations were formulated, the most important of which was the management of hospitals, increasing attention to the physical environment in the hospital, including elevators, a garage, and a resting place to enhance customer satisfaction in an oral way that contributes to enhancing the hospital's reputation